Genome-wide analysis and functional annotation of chromatin-enriched noncoding RNAs in rice during somatic cell regeneration - Zhang, Yu-Chan; Zhou, Yan-Fei; Cheng, Yu; Huang, Jia-Hui; Lian, Jian-Ping; Yang, Lu; He, Rui-Rui; Lei, Meng-Qi; Liu, Yu-Wei; Yuan, Chao; Zhao, Wen-Long; Xiao, Shi; et al. (Genome Biology, 2022)
Plants have the remarkable ability to generate callus, a pluripotent cell mass that acquires competence for subsequent tissue regeneration. Global chromatin remodeling is required for this cell fate transition, but how the process is regulated is not fully understood. Chromatin-enriched noncoding RNAs (cheRNAs) are thought to play important roles in maintaining chromatin state. However, whether cheRNAs participate in somatic cell regeneration in plants has not yet been clarified. To uncover the characteristics and functions of cheRNAs during somatic cell reprogramming in plants, we systematically investigate cheRNAs during callus induction, proliferation and regeneration in rice. We identify 2284 cheRNAs, most of which are novel long non-coding RNAs or small nucleolar RNAs. These cheRNAs, which are highly conserved across plant species, shuttle between chromatin and the nucleoplasm during somatic cell regeneration. They positively regulate the expression of neighboring genes via specific RNA motifs, which may interact with DNA motifs around cheRNA loci. Large-scale mutant analysis shows that cheRNAs are associated with plant size and seed morphology. Further detailed functional investigation of two che-lncRNAs demonstrates that their loss of function impairs cell dedifferentiation and plant regeneration, highlighting the functions of cheRNAs in regulating the expression of neighboring genes via specific motifs. These findings support cis- regulatory roles of cheRNAs in influencing a variety of rice traits. cheRNAs are a distinct subclass of regulatory non-coding RNAs that are required for somatic cell regeneration and regulate rice traits. Targeting cheRNAs has great potential for crop trait improvement and breeding in future.